The effect of task conflict on job satisfaction with positive emotions as a mediating variable - Melenia, Syukuria; Sulastri, Sulastri (Human Resource Management Studies, 2023)
This study analyzes: (1) the effect of task conflict on job satisfaction among employees of PT. Kunango Jantan West Sumatra. (2) the effect of task conflict on positive emotion in PT. Kunango Jantan West Sumatra. (3) the effect of positive emotion on job satisfaction in employees of PT. Kunango Jantan West Sumatra. (4) the effect of positive emotion mediation on task conflict on job satisfaction among employees of PT. Kunango Jantan West Sumatra. The population in this study were all employees of PT. Kunango Jantan West Sumatra, totaling 256 people. While the number of samples amounted to 156 people. The analysis technique used is SEM analysis using SmartPLS. The results of the study show that: (1) task conflict has a positive and significant effect on job satisfaction for employees of PT. Kunango Jantan West Sumatra. (2) task conflict has a positive and significant effect on positive emotion on employees of PT. Kunango Jantan West Sumatra. (3) positive emotion has a positive and significant effect on job satisfaction for employees of PT. Kunango Jantan West Sumatra. (4) task conflict has a positive and significant effect on job satisfaction with positive emotion as a mediating variable for employees of PT. Kunango Jantan West Sumatra.